Simulação da etapa de desbaste por elementos finitos na laminação de longos - Isaac Rosa Soares (2010)
Technology investments to increase productivity and product quality has long been the focus of studies by companies given the high competitiveness. High surface and internal quality to the wire rods and bars is essential for the production of long products that will undergo subsequent cold deformation. Products that will be submitted to cold forming for automotive application, for example, are products of high responsibility and small defects can lead to premature rupture of thefinal product. The control and understanding of the variables could contribute to the hot rolling process stability and prevent the occurrence of defects in the final product. The aim is to study the effect of some rolling variables such as friction, gap, interstand tensions, roll diameter and shape of caliper through numerical model in the roughing mill of round bars mill. The dimensional results obtained of the model in each passreach acceptable approach in comparison with the samples supplied by a producer of commercial bars.